From Innovation Development to Implementation Evidence from the Community Innovation Survey - Jaumotte, Florence (OECD Economics Department Working Papers, 2005)
Innovation surveys provide a broad measure of the successful commercial introduction of new product and process innovations. The dual purposes of this paper are to establish whether survey-based measures of innovation are related to more widely used intermediate measures, such as R&D and patents, and to identify the principal factors that affect the probability of successful innovation. Cross-country panel data is used from the third European Community Innovation Survey (CIS3), with allowance made for possible differences by firm size and by sector of activity. The survey measures of innovative activity and success are found to be positively correlated with past R&D and patenting, suggesting that factors affecting the development of innovations also affect their subsequent implementation. The availability of qualified personnel and private financing, less rigid product and labour market regulations, greater co-operation in the innovation process and public financial support are all found to be positively associated with the proportion of successful innovators for at least some sectors and firm sizes. Innovation in small firms is found to be more dependent on co-operation and the availability of finance than in larger firms